PEMILIHAN SUPPLIER BAHAN BAKU SERBUK BESI (FERRO SULPHATE) PADA PT. AM MENGGUNAKAN METODE ANALYTIC NETWORK PROCESS (ANP) - Adistia Marshalidia; Saptono Kusdanu Waskito; Darfial Guslan (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
PT AM is a company that makes blood enhancers derived from iron powder raw materials (Ferro Sulfate). PT AM requires raw materials from suppliers for the manufacture of blood enhancers. CV HM is a supplier of iron powder raw materials (Ferro Sulfate) dismissed because it has a poor assessment in supplying raw materials to PT AM. PT AM invited new vendors and received 4 (four) prospective vendors, namely CV MTJ, CV GML, CV AKI and CV ZMI. PT AM does not have a good method to determine which supplier selection to choose. The author analyzes supplier selection with criteria such as price, quality, flexibility, and delivery. This study used the Analytic Network Process (ANP) method with the results obtained were CV MTJ got a value of 0.4, CV AKI got a value of 0.3, CV ZMI got a value of 0.3 and CV GML got a value of 0.3, From the results of the ANP calculation, the winner is CV MTJ which has the highest score among the 4 (four) other suppliers, namely 0.4 final score.